2020
DOI: 10.1002/adfm.202009431
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Zwitterionic Cream Gel for Effective Prevention of Postoperative Adhesion

Abstract: Postoperative peritoneal adhesions are frequent complications for almost any type of abdominal and pelvic surgery. This leads to numerous medical problems and a huge financial burden to the patients. Current anti‐adhesion strategies focus mostly on physical barriers including films and hydrogels. However, they can only alleviate or reduce adhesions to a certain level and their applying processes are far from ideal. This work reported the development of a biodegradable zwitterionic cream gel presenting a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 45 publications
0
67
0
Order By: Relevance
“…Zwitterionic hydrogel showed both much faster recovery rate and better hair growth ( Figure 21 a). For inside wound or potential postoperative adhesion, Zhang et al [ 171 ] prepared pCBAA cream-gel with a biodegradable BAC crosslinker to further improve resistant peritoneal adhesion ( Figure 21 b).…”
Section: Biomedical Applications Of Zwitterionic Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zwitterionic hydrogel showed both much faster recovery rate and better hair growth ( Figure 21 a). For inside wound or potential postoperative adhesion, Zhang et al [ 171 ] prepared pCBAA cream-gel with a biodegradable BAC crosslinker to further improve resistant peritoneal adhesion ( Figure 21 b).…”
Section: Biomedical Applications Of Zwitterionic Hydrogelsmentioning
confidence: 99%
“…On days 7 and 14 post-surgery, adhesions were observed in the untreated control and intercede film groups, while no adhesion was observed in rats treated with cream-gel. Reproduced with permission from [ 171 ]. Copyright 2020 Wiley-VCH GmbH.…”
Section: Figurementioning
confidence: 99%
“…anti-adhesion, 36,37 antibacterial wound dressing, 38 etc. Chitosanbased hydrogels also have been widely used in the biomedical field due to their excellent biocompatibility, biodegradability, and good ability to kill bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Injectable zwitterionic hydrogels have been developed to prevent adhesions; however, the controllability of the gelation process in situ is a challenge that must be overcome [ 13 ] (Figure 1a; Table S1, Supporting Information). Furthermore, it has been recently reported that the uncontrolled recruitment of GATA6 + cavity macrophages leads to collagen deposition and postsurgical adhesion formation.…”
Section: Introductionmentioning
confidence: 99%